Application of STEAM in the Teaching of Symmetry and Reflection Using Augmented Reality (European Journal of Pure and Applied Mathematics, 2026)
This study explores the integration of Augmented Reality (AR) within a STEAM (Science, Technology, Engineering, Arts, and Mathematics) framework to enhance the teaching and learning of symmetry and reflection in geometry among Colombian secondary school students. Using a qualitative action research design, the study involved 22 sixth-grade students in Barranquilla, employing participant observation and semi-structured interviews to analyze students’ understanding, attitudes, and problem-solving processes. The results revealed that AR significantly improved students’ motivation, visualization skills, and conceptual understanding of geometric transformations. The interdisciplinary STEAM approach enabled meaningful connections between mathematics, science, technology, and art, fostering creativity, computational thinking, and collaboration. However, challenges emerged related to students’ initial mathematical foundations and the complexity of interdisciplinary integration. The findings underscore the transformative potential of AR and STEAM to enrich geometry education, while emphasizing the need for teacher training and curriculum design that support interdisciplinary and technology-enhanced learning. This research contributes practical and theoretical insights into how digital innovation can strengthen mathematical competencies and promote holistic, contextualized learning experiences
Keywords: STEAM education; augmented reality; geometry teaching; symmetry; reflection